2015
DOI: 10.1182/blood.v126.23.2120.2120
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Elderly Patients with Acute Myeloid Leukemia Undergoing Induction Chemotherapy

Abstract: Aims: In elderly patients with acute myeloid leukemia (AML), complete remission (CR) rate following intensive chemotherapy is approximately 45%, considerably lower than in younger patients, with a shorter duration of remission and high treatment-related mortality (30-50%). Median survival is about 12 months. Intensive chemotherapy is indicated in a small proportion of "fit" elderly patients. In a phase III, prospective, randomized, open-label, multicenter trial designed to assess the efficacy of post-remission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Interestingly, we found that baseline factors such as fatigue, gender, comorbidities, bone marrow blasts, and secondary AML were not related to HRQoL in one study 24. However, other studies showed these factors along with others to be correlated to HRQoL, such as baseline hemoglobin (Hg) levels and scores of QOL-E functional ( r =0.0216, P =0.14), fatigue ( r =0.256, P =0.002), and disease specific ( r =0.247, P =0.010) were shown to be statistically correlated.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Interestingly, we found that baseline factors such as fatigue, gender, comorbidities, bone marrow blasts, and secondary AML were not related to HRQoL in one study 24. However, other studies showed these factors along with others to be correlated to HRQoL, such as baseline hemoglobin (Hg) levels and scores of QOL-E functional ( r =0.0216, P =0.14), fatigue ( r =0.256, P =0.002), and disease specific ( r =0.247, P =0.010) were shown to be statistically correlated.…”
Section: Resultsmentioning
confidence: 76%
“…The HRQoL results from the four original RCTs informed the reviewers that some NIC treatments achieved a meaningful improvement in the fatigue of EORTC QLQ-C30, while other patients achieved meaningful improvement in both fatigue (cycles 7 and 9) and GHS 9,17,24–26. Patients aged ≥60 years with MDS or chronic myelomonocytic leukemia (intermediate 1/2, or high risk), who were ineligible for intensive treatment, showed a significant improvement in their PF and borderline improvement in GHS of EORTC QLQ-C30 17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation